2007
DOI: 10.1161/circulationaha.107.693382
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-I Is Crucially Involved in Lipopolysaccharide-Induced Atherosclerosis Development in Apolipoprotein E–Knockout Mice

Abstract: Background-Lipopolysaccharide (LPS), which is released from Gram-negative bacteria on multiplication or lysis, aggravates atherosclerosis in humans and rodents by inducing inflammation via toll-like receptors. Because apolipoprotein C-I (apoCI) enhances the LPS-induced inflammatory response in macrophages in vitro and in mice, we investigated the effect of endogenous apoCI expression on LPS-induced atherosclerosis in mice. Methods and Results-Twelve-week-old apoe Ϫ/Ϫ apoc1 Ϫ/Ϫ and apoe Ϫ/Ϫ apoc1 ϩ/ϩ mice recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 51 publications
4
70
1
Order By: Relevance
“…By enhancing the biological response toward LPS and Gram-negative bacteria, apoCI improved the antibacterial attack, reduced bacterial outgrowth, and protected against intrapulmonal Klebsiella pneumoniae -induced fatal sepsis ( 19 ). Moreover, by enhancing the systemic infl ammatory state, apoCI aggravated LPS-induced atherosclerosis in hyperlipidemic apoE-defi cient mice ( 20 ). We were able to extrapolate these fi ndings to humans by showing that plasma apoCI and apoCI-derived peptides.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…By enhancing the biological response toward LPS and Gram-negative bacteria, apoCI improved the antibacterial attack, reduced bacterial outgrowth, and protected against intrapulmonal Klebsiella pneumoniae -induced fatal sepsis ( 19 ). Moreover, by enhancing the systemic infl ammatory state, apoCI aggravated LPS-induced atherosclerosis in hyperlipidemic apoE-defi cient mice ( 20 ). We were able to extrapolate these fi ndings to humans by showing that plasma apoCI and apoCI-derived peptides.…”
mentioning
confidence: 77%
“…We previously reported that apoCI interacts with different forms of LPS from Salmonella minnesota [i.e., full-length wild-type LPS, and the truncated Re595 LPS, containing the lipid A moiety and some KDO sugars ( 19 )], but more recently we also found that apoCI interacts with different types of LPS from Escherichia coli [i.e . , O55:B5 LPS ( 20 ) and J5 LPS (Berbée and Rensen, unpublished observations)]. ApoCI thus interacts with both fulllength, wild-type LPS and truncated forms of LPS, which indicates that the lipid A/KDO moiety of the LPS molecule contains the crucial elements for interaction with apoCI.…”
Section: Downloaded Frommentioning
confidence: 96%
“…Intravenously injection of endotoxins has been shown to enhance the uptake of oxidized LDLs through increased expression of scavenger receptors [23]. In an apolipoprotein E-deficient mouse model, LPS injections were shown to increase the size of atherosclerotic lesions and were supported by T cell-mediated B cell activation [24] as well as by apolipoprotein CI-induced inflammation [25]. In a rabbit model, systemic inflammation induced by LPS was shown to cause intimal hyperplasia and increased expression of TLR4 and human antigen R [26]; LPS, through TLR4, activated p38 mitogen-activated protein kinase and nuclear factor-κB pathways, and upregulated expression of the Fcα/μ receptor in human macrophages, which promotes the formation of foam cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…A s an associate research scientist in Alan Tall's group at Columbia University, New York, Marit Westerterp's research has been focused on atherosclerosis and the molecular mechanisms of cholesterol efflux and transport [1][2][3][4][5] -a subject she will continue to pursue in her upcoming role as associate professor at the University of Groningen in the Netherlands.…”
Section: Promising Young Investigatorsmentioning
confidence: 99%